Imaging of In Vitro and In Vivo Neurons in Drosophila Using Stochastic Optical Reconstruction Microscopy. Issue 7 (21st July 2021) - Inal, Melissa Ana; Bui, Kathy Clara; Marar, Abhijit; Li, Shaoheng; Kner, Peter; Kamiyama, Daichi
Abstract: The Drosophila melanogaster brain comprises different neuronal cell types that interconnect with precise patterns of synaptic connections. These patterns are essential for the normal function of the brain. To understand the connectivity patterns requires characterizing them at single‐cell resolution, for which a fluorescence microscope becomes an indispensable tool. Additionally, because the neurons connect at the nanoscale, the investigation often demands super‐resolution microscopy. Here, we adopt one super‐resolution microscopy technique, called stochastic optical reconstruction microscopy (STORM), improving the lateral and axial resolution to ∼20 nm. This article extensively describes our methods along with considerations for sample preparation of neurons in vitro and in vivo, conjugation of dyes to antibodies, immunofluorescence labeling, and acquisition and processing of STORM data. With these tools and techniques, we open up the potential to investigate cell‐cell interactions using STORM in the Drosophila nervous system. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of Drosophila primary neuronal culture and embryonic fillets Basic Protocol 2 : Immunofluorescence labeling of samples Basic Protocol 3 : Single‐molecule fluorescence imaging Basic Protocol 4 : Localization and visualization of single‐molecule data Supporting Protocol : Conjugation of antibodies with STORM‐compatible dyes